Identification of the Key Enzymes in WL Gum Biosynthesis and Critical Composition in Viscosity Control - Li, Hui; Zhang, Zaimei; Liu, Jianlin; Guo, Zhongrui; Chen, Mengqi; Li, Benchao; Xue, Han; Ji, Sixue; Li, Hang; Qin, Lijian; Zhu, Ling; Wang, Jiqian; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
As an important microbial exopolysaccharide, the sphingan WL gum could be widely used in petroleum, food, and many other fields. However, its lower production is still limiting its wider application. Therefore, to gain insights into the bottlenecks of WL gum production by identifying the key enzymes in the WL gum biosynthesis pathway, more than 20 genes were over-expressed in Sphingomonas sp. WG and their effects on WL gum production and structure were investigated. Compared to the control strain, the WL gum production of welB over-expression strain was increased by 19.0% and 21.0 % at 36 h and 84 h, respectively. The WL gum production of both atrB and atrD over-expression strains reached 47 g/L, which was approximately 34.5% higher than that of the control strain at 36 h. Therefore, WelB, AtrB, and AtrD may be the key enzymes in WL production. Interestingly, the broth viscosity of most over-expression strains decreased, especially the welJ over-expression strain whose viscosity decreased by 99.3% at 84 h. Polysaccharides' structural features were investigated to find the critical components in viscosity control. The uronic acid content and total sugar content was affected by only a few genes, therefore, uronic acid and total sugar content may be not the key composition. In comparison, the acetyl degrees were enhanced by over-expression of most genes, which meant that acetyl content may be the critical factor and negatively correlated with the apparent viscosity of WL gum. This work provides useful information on the understanding of the bottlenecks of WL gum biosynthesis and will be helpful for the construction of high WL gum-yielding strains s and rheological property controlling in different industries.